Efektivitas Gosok Gigi Massal dan Pendidikan Kesehatan Gigi Mulut Pada Anak Usia 7-11 Tahun di SD Inpres Unggulan BTN Pemda - Arfiah Jauharuddin; Rumaisha Soumena; Suciyati Sundu; Dewi Sartika; Hasrini Hasrini (FKIP, Universitas Palangka Raya, 2024)
Maintenance of oral health is one way to improve health. The mouth is not just an entry point for food and drink but the function of the mouth is more than that and not many people realize the big role the mouth plays for one's health and well-being.The output target of this activity is the implementation of the School-Age Health Degrees Improvement Program.The method used in this research is observation, counseling and evaluation. The result on brushing teeth properly and correctly Schoolat 174Murni, the children realized that brushing their teeth from an early age was very important, the children were able to brush their teeth properly and correctly even though it was not optimal, so that children had knowledge from an early age about brushing teeth properly and properly. providing support to children in terms of health is very important because it can become a habit for life later.Obtained from counseling on proper and proper tooth brushing at schoo at 174 Murni is that children have realized that brushing their teeth from an early age is very important, children can brush their teeth properly and correctly even though they are not maximized, giving support to In terms of health, children are very important because they can become a habit for their future lif